Mediating Role of Enjoyment in the Associations between Social Support and Participation in Physical Activity among Female Adolescents - Sadeghi Pour, Niki; Marjan Baniasadi, Tayebeh (International Journal of Sport Studies for Health, 2025)
Objective:  This study focused on examining the connections between social support and physical activity participation, with enjoyment identified as a mediating variable.Methods and Materials: This research employed a descriptive-correlational approach utilizing structural equation modeling. A sample of 384 adolescent girls was selected through convenience sampling. Standardized assessment tools were used to measure the research variables, and the data analysis was performed using Smart PLS statistical software version 4, with a significance threshold set at 0.05.Findings: The path analysis results indicate a significant positive structural relationship between physical activity (P=0.000, T=8.54, b=0.53) and enjoyment (P=0.000, T=10.23, b=0.45) in relation to social support. Additionally, a significant positive structural relationship exists between the enjoyment and physical activity (P=0.000, T=6.84, b=0.33). In addition, enjoyment serves as a significant mediating factor in the relationship between the social support and physical activity, with a p-value of 0.000, a t-value of 4.58, and a b coefficient of 0.16.Conclusion: The findings of this study highlight the profound influence of the home and family environment on the physical activity trajectories of children and adolescents, emphasizing that parental support plays a vital role in establishing an active lifestyle that can predict future levels of physical activity.